2017
DOI: 10.5539/sar.v6n4p12
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Seed Policies for On-Farm Agro-Biodiversity in Ethiopia and Uganda

Abstract: Across East Africa, national seed policies and commercial seed enterprises have focused on increasing farmers" access to modern seed varieties. These new varieties are developed and delivered to farmers via the formal seed system, which is comprised of government and private sector seed breeders, processors, and vendors. However, the formal seed system only provides a small share (<20%) of smallholders" seed in the region. Most farmers source seed from informal seed systems, including own-saved seed, exchanges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
(32 reference statements)
0
17
1
Order By: Relevance
“…Seed policies and seed laws are mainly concerned with regulating the formal seed sector, though there have been concerns raised around how such legislation may affect how farmers' seed systems function [31]. If seed legislation prohibits the sale of crop varieties that were not registered in the national or regional varietal list, or of seed that was not certified or quality assured, informal traders may be unable to operate legally [32]. Reviews of seed policy impacts on informal seed systems tend to focus on biodiversity-what can be circulated, rather than who can take part in the circulation [33]; but these reviews help clarify how legislative frameworks may affect informal traders, and where there may be scope to work with them more closely.…”
Section: Legal and Donor Insight Into Embracing Trader Rolesmentioning
confidence: 99%
“…Seed policies and seed laws are mainly concerned with regulating the formal seed sector, though there have been concerns raised around how such legislation may affect how farmers' seed systems function [31]. If seed legislation prohibits the sale of crop varieties that were not registered in the national or regional varietal list, or of seed that was not certified or quality assured, informal traders may be unable to operate legally [32]. Reviews of seed policy impacts on informal seed systems tend to focus on biodiversity-what can be circulated, rather than who can take part in the circulation [33]; but these reviews help clarify how legislative frameworks may affect informal traders, and where there may be scope to work with them more closely.…”
Section: Legal and Donor Insight Into Embracing Trader Rolesmentioning
confidence: 99%
“…The legislations also conceptualize farmers' rights as an important protection for smallholder agricultural production and food security. Indeed, the government is committed to implement farmers' rights (Feyissa, 2006) and its policy of pluralistic seed system that aims to ensure complementarity of formal and farmers' seed systems (MoA and ATA, 2013; Otieno et al, 2017). This makes Ethiopia exceptional with regard to a global survey recently conducted by the ITPGRFA Secretariat that concluded that the conflict between national and international policies (e.g., MTAs, IPRs, and Farmers' Rights) is one of the major bottlenecks in the Treaty's MLS (Kell, Marino, & Maxted, 2017).…”
Section: Ethiopian Pgrfa and Its Governancementioning
confidence: 99%
“…Very few seed companies operate in seed distribution due to lack of a liberalized seed market policy in Ethiopia (Alemu, 2011b; MoA, 2019b; Scoones & Thompson, 2011). The government has chosen a policy that promotes pluralistic seed systems aiming at implementing farmers' rights and on‐farm management of crop diversity (Alemu, 2016; Otieno et al, 2017). Ethiopian negotiators have influenced early regional and international negotiations in favor of national control over own genetic resources, promoting farmers', and community rights (Chasek, McGraw, & Prather, 1996; de Fontaubert, Ivers, Megateli, & Prather, 1997; Fry, Ivers, Megateli, & Prather, 1998; Gebre Egziabher et al, 2011).…”
Section: Historical Political and Economic Factors Influencing Pgrfmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of smallholder farmers in Uganda lack a sustainable and reliable seed supply system to ensure quality agricultural production and productivity (The African Seed Access Index (TASAI), 2015). 80 per cent of seed used by Ugandan farmers is obtained locally through own saved seed; exchange with neighbours; community seed banks; custodian farmers; and from the local markets (Otieno et al, 2016). Local seed systems therefore play an important role in providing diverse seed to farmers.…”
Section: Introductionmentioning
confidence: 99%